Pengaruh Storytelling Marketing, Brand Trust dan Price Terhadap Purchase Intention Produk Skintific pada Aplikasi Belanja Online Shopee dalam Perspektif Bisnis Islam - Anggun Wijayanti; Supaijo Supaijo; Weny Rosilawati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The promising development of the beauty product industry in Indonesia has led many beauty brands to decide to market their products in the country. In 2023, the Skintific brand became the winner in the facial serum subcategory, achieving a market share of 16.66%. The researcher chose to study Skintific to understand why consumers purchase Skintific products. This research uses a quantitative method. The sample size of this study is 98 respondents, with data collection techniques utilizing both primary and secondary data. Primary data was obtained through the distribution of questionnaires and observation, while secondary data was used as well. Data processing in this study uses IBM SPSS version 23.